Formulation and Antioxidant Activity of Gotu Kola Jelly Candy with Plant-based Polymers as a Gelling Agent - Devi, Dwitya Devi Nurlistyo; Darsih, Cici; Yuniarti, Nunung; Ardiningtyas, Bondan; Laksitorini, Marlyn Dian (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Centella asiatica or gotu kola has a long history as a brain supplement. Gotu kola supplements are sold as liquid and dried extract which is less attractive for a younger generation. Jelly candy is an alternative dosage form with better acceptability across ages. However, the use of animal-derived polymers such as pork gelatine in the candy restricts those who practice vegetarian and halal lifestyles from consuming the products. This study aims to explore plant-based polymers glucomannan and kappa-carrageenan as gelling agents in the preparation of gotu kola jelly candy. Preparation of the jelly candy formula was designed based on Simplex Lattice Design. Evaluation of physical characteristics of jelly candy includes organoleptic, weight uniformity, moisture content, pH, and elasticity. The antioxidant activity of gotu kola before and after the manufacturing process was evaluated. The results showed that a combination of kappa-carrageenan 1.33% and glucomannan 0.67% is the optimum formula. Adding more proportion of kappa-carrageenan reduced jelly elasticity and moisture content. While adding glucomannan improved its elasticity responses but increased moisture content. Evaluation of the antioxidant activity of gotu kola in jelly candy suggested that gotu kola experienced a significant reduction in antioxidant activity following the production process. The IC50 of the crude extract initially was129.23 ppm while post jelly candy manufacturing, the IC50 increased to 197.49 ppm. This study suggested that improvement in extraction and production processes is necessary to maintain gotu kola antioxidant activity.